From classroom to screen: a cross-sectional study on medical students’ first experiences with e-learning during the COVID-19 pandemic - Khojasteh, Laleh; Karimian, Zahra; Nasiri, Elham; Sharifzadeh, Sedigheh; Farrokhi, Majid Reza (Frontiers in Education, 2025)
IntroductionFollowing the Coronavirus Disease 2019 (COVID-19) pandemic, most universities around the world transitioned from in-person classrooms to online learning methods. This study aimed to explore the initial experiences of medical students with e-learning during the pandemic at Shiraz University of Medical Sciences in Iran, as well as to identify differences in students’ general perceptions based on their demographic characteristics.MethodsThis cross-sectional study was conducted on 507 medical students during the COVID-19 pandemic. To gather information for this study, a questionnaire created by the researchers was used, which consisted of six variables and 26 items on a Likert scale. The content validity of the questionnaire was assessed using Content Validity Index (CVI) and Content Validity Ratio (CVR). The reliability of the questionnaire, based on the internal consistency of the questions, was confirmed by a Cronbach’s alpha of 97.5%. Data were analyzed using a one-sample t-test, independent t-test, ANOVA, and MANOVA.ResultsStudents had satisfactory e-learning experiences, and the average of e-learning components was: technological facilities (4.29 ± 1.13), technical support (4.00 ± 1.08), e-content quality (3.84 ± 1.05), synchronous education (3.59 ± 1.31), asynchronous education (3.73 ± 1.20), and teacher-student interaction (3.63 ± 1.32). Students’ perceptions of the e-learning environment were shown to be substantially connected to their age, access to electronic devices, computer proficiency, prior experience regarding e-learning, and the school in which they are studying, respectively (P = 0.027). Furthermore, students who had access to a computer were more satisfied than those who only had access to a mobile phone (P < 0.001). In medical schools where teacher-student interaction was better, more satisfaction was observed (P < 0.001). The gender factor had no effect on students’ views.ConclusionEven though it seems like e-learning can be a good substitute for or complement to face-to-face training, the most important thing that makes this method more effective is the interaction between the teacher and the students.